Analysis of materialism, fashion clothing, and recreational shopper identity - Endang Ruswanti (Universitas Hayam Wuruk Perbanas, 2014)
This study examines the effect of materialism on fashion clothing and recreational shopper identity. This is done by a survey with the total sample of 71 respondents. It consists of 45 respondents male and 26 female; while 56 respondents earn more than 5 million, 12 respondents earn over 3 millio, and 3 respondents earn above 10 million. These respondents are the executive students Esa Unggul University, Jakarta. The ages of the respondents are between 18 and 57 years. The sample was taken based on purposive sampling of respondents who like fashion and earn for their living between 2 million to > 10 million. The analysis was done by using multiple regressions with SPSS 17. It shows that materialism significantly has positive effect on fashion clothing and materialism affectsconsumers’ recreational shopper identity. The managerial implication is that the average age of the respondents is 31-50 and they have an income above 5 million who love shopping in malls and buying fashion clothes. Therefore, the malls offer more varied products that consumers need so that the consumers who have a tendency of being materialism like fashion shopping in the malls always come and they are expected to be loyal to going to the malls. The fashion manufacturer needs to pay to the strategy for multiplying the product variety of fashion in accordance suited with the age of 31-50 years.